Exercise Increases and Browns Muscle Lipid in High-Fat Diet-Fed Mice - Morton, Tiffany L.; Galior, Kornelia; McGrath, Cody; Wu, Xin; Uzer, Gunes; Uzer, Guniz Bas; Sen, Buer; Xie, Zhihui; Tyson, David; Rubin, Janet; Styner, Maya (Frontiers in Endocrinology, 2016)
Muscle Lipid increases with high-fat feeding and diabetes. In trained athletes, increased muscle lipid is not associated with insulin resistance, a phenomenon known as the athlete’s paradox. To understand if exercise altered the phenotype of muscle lipid, female C57BL/6 mice fed CTL or high fat diet (HFD for 6 or 18 wk) were further divided into sedentary or exercising groups (CTL-E or HFD-E) with voluntary access to running wheels for the last 6 wk of experiments, running 6 h/night. Diet did not affect running time or distance. HFD mice weighed more than CTL after 18 wk (p<0.01). Quadriceps muscle TG was increased in running animals and in sedentary mice fed HFD for 18 wk (p<0.05). In exercised animals, markers of fat: Plin1, aP2, FSP27 and Fasn, were increased significantly in HFD groups. Ucp1 and Pgc1a, markers for brown fat, increased with exercise in the setting of high fat feeding. Fndc5, which encodes irisin, and CytC, were sensitive to exercise regardless of diet. Plin5 was increased with HFD and unaffected by exercise; The respiratory exchange ratio was 15% lower in the 18 wk HFD group compared with CTL (p<0.001) and 10% lower in 18 wk HFD-E compared to CTL-E (p<0.001). Increased Ucp1 and Pgc1a in exercised muscle of running mice suggests that a beige/brown fat phenotype develops, which differs from the fat phenotype that induces insulin resistance in high fat feeding. This suggests that increased muscle lipid may develop a ‘brown’ phenotype in the setting of endurance exercise training, a shift that is further promoted by HFD.